The Use of Stimulus Preference Assessments for Persons with Neurocognitive Disorder: A Literature Review. Issue 3 (3rd May 2020) - Wagner, Sandra; Buchanan, Jeffrey A.; Bailey, Jordan; Andresen, Felicia J.; Omlie, Christina
ABSTRACT: Objectives : Stimulus preference assessments are a systematic, observation-based approach for identifying preferences among individuals with impaired communication skills. The purpose of this paper is to provide a review of the existing empirical literature that has utilized these methods with persons who have neurocognitive disorder (NCD). Methods : Studies were identified by searching online databases using a variety of search terms. Articles were included in the review if they were peer-reviewed, in English, were empirical in nature, and conducted a stimulus preference assessment with older adults diagnosed with NCD. Results : Eleven articles met the search criteria. Results revealed that data from stimulus preference assessments could increase activity engagement, increase requests for preferred items, identify reinforcers, and reduce behavioral and psychological symptoms. Conclusions : A small body of empirical literature suggests that data derived from stimulus preference assessments can be used to improve the lives of persons with NCD and their caregivers. Additional research is needed, however, to determine how effectively these procedures can be implemented into everyday practice in long-term care facilities. Clinical Implications : Stimulus preference assessments may provide a clinically useful means for efficiently identifying preferences in persons with severe NCD who cannot verbalize their needs.